2012
DOI: 10.1177/1096348012436375
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Development of a New operational classification System For The Foodservice Industry

Abstract: The foodservice industry is large and diverse, demanding an adequate system for classifying its many different types of operations. There are many different classification systems in use by industry and researchers. Although many of the current systems offer certain benefits, some do not provide the necessary framework for researchers and some do not provide realistic groupings for purposes of industry benchmarking. Furthermore, in many cases, classification systems are not compatible with one another. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…There seems to be no consensus about the importance of this factor. Barber and Scarcelli (2009) found that consumers are indeed concerned with cleanliness and food safety. In particular, restrooms are found to be an important factor when assessing the cleanliness and hygiene of a restaurant.…”
Section: Cleanliness/hygienementioning
confidence: 99%
“…There seems to be no consensus about the importance of this factor. Barber and Scarcelli (2009) found that consumers are indeed concerned with cleanliness and food safety. In particular, restrooms are found to be an important factor when assessing the cleanliness and hygiene of a restaurant.…”
Section: Cleanliness/hygienementioning
confidence: 99%
“…In the quick-service restaurant (QSR) industry (which includes coffeehouse brands), advertising plays a vital role in attracting customers (Barrows & Vieira, 2012;Cao & Kim, 2015). Faced with increased competition, QSRs constantly strive to develop effective advertisements in order to promote their brands and gain customer loyalty (Duarte Alonso, O'Neill, Liu, & O'Shea, 2013;Magnini, Honeycutt, & Cross, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Barrows and Vieira (2013) provided recommendations for the development of a new operational classification system for the foodservice industry. An extensive comparative study of the existing classification showed that there was no uniform system of classification that would accurately differentiate between different types of foodservice establishments.…”
Section: Discussionmentioning
confidence: 99%